2009
DOI: 10.1039/b810617g
|View full text |Cite
|
Sign up to set email alerts
|

From microelectronics to molecular spintronics: an explorer's travelling guide

Abstract: We present in this article a broad overview of the fields of molecular electronics and molecular spintronics. This is supplemented by an pedagogical introduction which presents basic concepts of electronic transport and of microelectronics, which intends to show the most pressing issues that face the microelectronics industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 198 publications
(346 reference statements)
0
25
0
Order By: Relevance
“…In addition, using molecules to bridge graphene nanojunctions should furnish the array of expected applications of graphene electronics with a whole suite of new functionalities. [8][9][10] A crucial pending issue for the use of graphene nanoelectronics is the difficulty in controlling the edges of graphene sheets. This could not only influence the electronic properties of the graphene electrodes but it could also change arbitrarily the coupling and switching functionality of the molecules attached.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using molecules to bridge graphene nanojunctions should furnish the array of expected applications of graphene electronics with a whole suite of new functionalities. [8][9][10] A crucial pending issue for the use of graphene nanoelectronics is the difficulty in controlling the edges of graphene sheets. This could not only influence the electronic properties of the graphene electrodes but it could also change arbitrarily the coupling and switching functionality of the molecules attached.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Recent systematic ab initio calculations of the freestanding binary Mo 4−x Fe x clusters in the whole range of concentrations have shown that certain isomers can be good candidates for molecular electronic devices. 18 In particular, it has been shown that the stable linear isomer of Mo 2 Fe 2 is formed by two Fe atoms separated by a nearly nonmagnetic Mo dimer.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, these two disciplines did not overlap significantly [7][8][9]. However, more recently, a link has been established between spintronics and molecular electronics as interest has grown in the use of magnetically ordered molecular clusters for electronic transport [10][11][12][13][14][15]. For example, nanosized Fe-or Mn-based single molecule magnets (SMMs), which can potentially serve as magnetically-functional units or logic devices, have been extensively studied [16][17][18][19][20].…”
mentioning
confidence: 99%